The Geography of Multinationals : Studies in the Spatial Development and Economic Consequences of Multinational Corporations. - Taylor, Michael, 1946 February 28- (Routledge Library Editions: International Business., 2013)
The volume is divided into two parts. In the first each of the chapters considers a particular aspect of the problem of how multinational corporations have developed. In the second part the chapters consider different aspects of the economic and social impacts of these corporations. The common theme that links all the papers is their emphasis on careful historical analysis of different forms of spatial organisation and their transformation into other, different forms.